2018
DOI: 10.21037/jtd.2018.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Combining radiation plus immunotherapy to improve systemic immune response

Abstract: Over the past decade, the fields of oncology have made great strides in therapies. The development of new therapeutics and increased understanding of the role of the immune system in the development and treatment of cancer has led to increased collaboration between oncologic fields. Recent technologic advancements in radiation therapy (RT), including stereotactic beam radiation therapy (SBRT), have improved local control and offer an alternative to surgery for the control of oligometastatic disease. Immunother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 50 publications
1
32
0
1
Order By: Relevance
“…However, radiation is also known to have a wide variety of immunomodulatory effects, and as such its potential for overcoming treatment resistance or improving the effectiveness of systemic therapies—particularly immunotherapy—is increasingly being recognized. 1 2 Indeed, high-dose stereotactic XRT (H-XRT) has been used in attempts to transform tumors into in situ vaccines by eliciting the release of neoantigens from the tumor that in turn prime T cells and contribute to T cell repertoire diversity. 3 Others have found that H-XRT in combination with anti-cytotoxic T-lymphocyte associated protein 4 (CTLA-4) can have a significant survival advantage in a murine 4T1 metastatic breast cancer model.…”
Section: Introductionmentioning
confidence: 99%
“…However, radiation is also known to have a wide variety of immunomodulatory effects, and as such its potential for overcoming treatment resistance or improving the effectiveness of systemic therapies—particularly immunotherapy—is increasingly being recognized. 1 2 Indeed, high-dose stereotactic XRT (H-XRT) has been used in attempts to transform tumors into in situ vaccines by eliciting the release of neoantigens from the tumor that in turn prime T cells and contribute to T cell repertoire diversity. 3 Others have found that H-XRT in combination with anti-cytotoxic T-lymphocyte associated protein 4 (CTLA-4) can have a significant survival advantage in a murine 4T1 metastatic breast cancer model.…”
Section: Introductionmentioning
confidence: 99%
“…Only two patient received intracranial stereotactic radiotherapy and no patients received extracranial stereotactic radiotherapy. Further data on concurrent immunotherapy and RT are anticipated with numerous trials ongoing worldwide . It should be noted, this study did not analyze the precise timing of RT with respect to the date of nivolumab administration and hence does not provide information on whether nivolumab administration was delayed for RT.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the 4.9% incidence of mediastinal recurrence was lower than that would be expected historically, raising the hypothesis of distant immune effects with the use of SBRT. Indeed, the possibility of tumor antigen presentation with ablative treatments and its impact on immunotherapeutic treatments is yet to be fully explored, and there are ongoing clinical trials combining SBRT with immunotherapy in lung cancer …”
Section: Opening Statementsmentioning
confidence: 99%